Subsequent application of bonding agents to a one-step self-etch adhesive - Its effect with/without previous light-curing - Tichy, Antonin; Hosaka, Keiichi; Bradna, Pavel; Ikeda, Masaomi; Abdou, Ahmed; Nakajima, Masatoshi; Tagami, Junji (Dental materials, 2019)
OBJECTIVE: The influence of light-curing of a one-step self-etch adhesive (1-SEA) prior to the application of different bonding agents (BA) on the micro-tensile bond strength (μTBS) to dentin after 24h and thermal cycling was investigated. Additionally, the degree of conversion was evaluated using Fourier-transform infrared spectroscopy. METHODS: Three ion-releasing BAs, BZF-21 (experimental BA), Clearfil SE Protect (CSP), and FL-Bond II (FL-II), were applied subsequently to G-Premio Bond (1-SEA, GPB). Prior to their application, GPB was either light-cured (10s, 1000mW/cm2) or remained uncured. GPB was used as a control and Clearfil SE Bond 2 (CSE2) as a gold-standard 2-step reference. After resin-composite build-up and 24-h water storage (24h), half of the specimens were subjected to 15,000 thermal cycles (TC). Then, the specimens were sectioned into beams and tested under tensile load (1mm/min). The acquired data were analyzed using a 2-way ANOVA and Student's t-test with Bonferroni correction, and a two-parameter Weibull analysis, α=0.05. RESULTS: The μTBS of GPB increased significantly in the uncured groups with BZF-21 (24h: p<0.001, TC: p<0.001) and CSP (24h: p=0.039, TC: p<0.001), and in the light-cured group with CSP after TC (p=0.044). The groups with FL-II were not significantly different from GPB (p=1). No significant difference was found between CSE2 and the uncured groups GPB+BZF-21 (24h: p=1, TC: p=0.452) and GPB+CSP (24h: p=0.671, TC: p=0.566). SIGNIFICANCE: BZF-21 and CSP improved the μTBS of GPB to dentin both immediately and after TC. Higher μTBSs were obtained when GPB remained uncured prior to BA application.
Keywords: vazba zubní; Self-etch adhesive systems; pryskyřičné cementy; Dental Bonding; Micro-tensile bond strength; Failure mode; Curing Lights, Dental; lidé; Dentin-Bonding Agents; Bio-active; zubní cementy; Tensile Strength; Two-step; Composite Resins; složené pryskyřice; Dentin; Materials Testing; Degree of conversion; dentin; One-step; stomatologické polymerizační lampy; testování materiálů; Dental Cements; dentinová adheziva; Adhesion; Resin Cements; Thermal cycling; pevnost v tahu; Humans